Receiving the Gift of Laughter: How Joy Transforms the Life of an Inclusive Congregation - Tamminga, K. S. (Koos) (Journal of disability & religion, 2020)
In this article, the role of laughter in Christian communities is studied, specifically in its relation to the inclusion of people with disabilities in these communities. A case study is presented and reflected upon from a socio-philosophical framework. Subsequently, theological considerations on laughter are introduced and discussed. The concluding argument of the article is that laughter should be considered a charisma to adequately understand and value its role in (Christian) communities.